Hormonal profile and haematological parameters of male wistar albino rats treated with methanloic extract of Parthenium hysterophorus L. - Saha, Priyanka; Yadav, Neha; Kumari, Suruchi; Raipat, Bharti Singh; Sinha, M.P (Journal of Experimental Sciences, 2013)
Changes in hormonal and haematological level were assessed in male wistar albino rats treated with methanolic extract of Parthenium hysterophorus L. The result showed that methanolic extract treatment caused a significant (p < 0.01) reduction of 20 % and 40% in total RBC count (6.25 ± 0.025 to 5 ± 0.5 x 106/µL) and haemoglobin (17.1 ± 0.1892 to 10.2 ± 0.79 g / dL) respectively in treated rats over control. Unlike haematological parameters, hormonal profile showed a significant increase of 40% (p < 0.05), 200% (p < 0.01), 100% (p < 0.01) and 45.08% (p < 0.001) in follicle stimulating hormone, leutinizing hormone, prolactin and testosterone respectively. The reduction of blood parameters is due to less haemopoiesis or induction of anemia. The increase in hormone level may be a cause of prostate cancer in wistar albino rats.